Importance of Exposure Level for Toxicological Risk Assessment - Drexler, Hans; Shukla, Anuradha (Springer International Publishing, 2021)
A health risk for an individual due to an exposure to a hazardous substance depends upon the properties of the substance, the amount of the substance, and the susceptibility of the individual. If an individual is susceptible to a particular hazardous substance only the amount of the substance determines the risk resulting from the exposure to this substance. In the case of local effects the concentration of the hazardous substance in the environment and the duration of the contact determine the risk, with the exception of allergic reactions where the susceptibility is more significant. In the case of systemic effects only the internal exposure or dose is relevant for the risk. Therefore, it is important for the marker of exposure to be a good surrogate for the dose in the target organ. If appropriate methods are available a biological monitoring is more significant for risk assessment as compared to ambient monitoring. If biomarkers of effect are available not only the general but also the individual risk can be assessed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Dermal absorption; DNA adducts; Effect monitoring; Individual exposure; Internal exposure; Protein adducts; Sensitization; Susceptibility